2005
DOI: 10.1890/04-1910
|View full text |Cite
|
Sign up to set email alerts
|

Global Models for Predicting Woody Plant Richness From Climate: Development and Evaluation

Abstract: There have been few attempts to generate global models of climate–richness relationships, and fewer still that aim to predict richness rather than fitting a model to data. One such model, grounded on theory (biological relativity to water–energy dynamics) is the interim general model (IGM1) of the climatic potential for woody plant richness. Here we present a second‐generation model (IGM2), and genus and family versions of both models. IGM1 describes horizontal climate–richness relationships based on climate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
215
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(233 citation statements)
references
References 15 publications
(56 reference statements)
16
215
2
Order By: Relevance
“…This bioinformatic database has recently been compiled ) at a spatial resolution of 0.58Â 0.58 cells (approx. 55.5 km) and contains 228 grid cells, of which 160 cells are included here as these are known to provide reasonable estimates of bird and woody plant species richness (Field et al 2005;. Distribution information on 1005 breeding bird species and 1417 woody plant species was included, and species richness of both taxa was estimated from this information for each grid cell.…”
Section: Materials and Methods (A) Species-richness Datamentioning
confidence: 99%
See 3 more Smart Citations
“…This bioinformatic database has recently been compiled ) at a spatial resolution of 0.58Â 0.58 cells (approx. 55.5 km) and contains 228 grid cells, of which 160 cells are included here as these are known to provide reasonable estimates of bird and woody plant species richness (Field et al 2005;. Distribution information on 1005 breeding bird species and 1417 woody plant species was included, and species richness of both taxa was estimated from this information for each grid cell.…”
Section: Materials and Methods (A) Species-richness Datamentioning
confidence: 99%
“…Vagrant bird species and species represented only by anecdotal records (n ¼ 60 species) were not included . Similarly, plants that are nonnative, 2.5 m or less in height at maturity, or that are not truly woody were excluded (Field et al 2005). To our knowledge, this database currently contains the most comprehensive information on bird and woody plant distributions at a regional scale in tropical Africa.…”
Section: Materials and Methods (A) Species-richness Datamentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have shown a remarkably strong association between contemporary climate and species richness (4,5,7,11,16,(26)(27)(28). According to the ''water-energy dynamics hypothesis,'' species richness at higher latitudes is controlled by the availability of ambient heat, whereas, in the thermally suitable tropics, water-and humidity-related variables are the main driving factors (4,5,28).…”
mentioning
confidence: 99%